1996
DOI: 10.1021/bi9610515
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Protein Chemical Analyses Demonstrate the Presence of C-Mannosylated Tryptophan in Intact Human RNase 2 and Its Isoforms

Abstract: Recently, the C-mannosylation of a specific tryptophan residue in RNase 2 from human urine has been reported [Hofsteenge, J., et al. (1994) Biochemistry 33, 13524-13530; de Beer, T., et al. (1995) Biochemistry 34, 11785-11789]. In those studies, identification of this unusual modification was accomplished by mass spectrometric and NMR spectroscopic analysis of peptide fragments. The evidence for the occurrence of C 2 -R-mannosyltryptophan [(C 2 -Man-)Trp] in the intact protein relied exclusively on the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 27 publications
(66 reference statements)
3
55
0
Order By: Relevance
“…Edman degradation of this peptide yielded at the fourth cycle a PTH-derivative that comigrated with PTH-(C 2 -Man-)Trp obtained from human RNase 2 ( Fig. 1C), a protein whose C-mannosylation has previously been extensively characterized (5)(6)(7).…”
Section: Resultsmentioning
confidence: 99%
“…Edman degradation of this peptide yielded at the fourth cycle a PTH-derivative that comigrated with PTH-(C 2 -Man-)Trp obtained from human RNase 2 ( Fig. 1C), a protein whose C-mannosylation has previously been extensively characterized (5)(6)(7).…”
Section: Resultsmentioning
confidence: 99%
“…One example is C-mannosylation of tryptophan residues within a WXXW motif. This modification also utilizes dolichol phosphate as the sugar donor (Doucey et al, 1998) and has thus far been found in RNase 2 (Loffler et al, 1996), IL-12, properdin, and other members of the complement protein family (Hofsteenge et al, 1999) (Hartmann andHofsteenge, 2000). C-mannosylation almost certainly occurs in the ER, but its timing and consequences for protein folding and activity are not known.…”
Section: Glycosylationmentioning
confidence: 99%
“…Eosinophil-deri~ed neurotoxin (El)N) is a member of thc pyrimidine-specific RNasc superfamily in vcrtcbratcs. It has the samc amino acid sequence as RNasc 2 and is also (,'-mannosylated [2]. The X-ray structure of recombinant EI)N [3] cxprcssed in E.rl~eri¢~ia (o/i was used to model thc g'-Iinkagc between nlannosc and Trp7 ( Figure 2).…”
Section: C-glycosylationmentioning
confidence: 99%